A fluorine-doped nanocatalytic material and its preparation method and application

Through the preparation of fluorine-doped nanocatalytic materials, the high cost and low stability of PEMFCs electrocatalysts are solved, the efficient utilization of platinum and the stability of the catalyst are achieved, and it is suitable for proton exchange membrane fuel cells.

CN115579481BActive Publication Date: 2024-12-24CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202211419944.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-14
Publication Date
2024-12-24
Estimated Expiration
2042-11-14

AI Technical Summary

Technical Problem

The high cost and low stability of existing proton exchange membrane fuel cell (PEMFCs) electrocatalysts limit their commercial applications, especially due to the shortage of platinum resources and the susceptibility of carbon support, resulting in the shedding of platinum particles and reduced activity.

Method used

Using fluorine-doped nanocatalytic materials, the catalyst is prepared by mixing carbon black and polytetrafluoroethylene and pyrolyzing in a tube furnace to form an F-doped carbon support, and then combined with platinum compounds by ultrasonic and water bath. Improve the dispersion of platinum and the number of active sites, and enhance the stability of the catalyst.

Benefits of technology

It effectively reduces the amount of platinum, improves the activity and stability of the catalyst, and achieves excellent oxygen reduction activity. It is suitable for proton exchange membrane fuel cells, and the preparation process is simple and easy to operate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115579481B_ABST
    Figure CN115579481B_ABST
Patent Text Reader

Abstract

The present invention discloses a fluorine-doped nanocatalytic material and a preparation method and application thereof. The ultra-low platinum fuel cell catalyst prepared by the present invention combines F-doped carbon material with platinum, and the non-precious metal active sites interact with the platinum active sites, thereby effectively reducing the amount of platinum. The C / F carrier is prepared by using F-doped carbon material, which increases the number of active sites and improves the catalyst activity. The F-doped carbon material is used as a carrier to improve the catalyst stability, and it is found that the F-containing carbon material is conducive to the anchoring of platinum and can also improve the dispersion of platinum in the catalyst. The preparation process is simple, easy to operate, and can achieve rapid preparation. It has excellent oxygen reduction activity and can be used in proton exchange membrane fuel cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fuel cell catalysts, and in particular relates to a fluorine-doped nanocatalytic material and a preparation method and application thereof. Background Art

[0002] In recent years, with the large-scale exploitation and utilization of fossil energy, fossil energy has become increasingly depleted and has brought about problems such as environmental pollution. The development of clean energy can effectively alleviate environmental pollution and energy crisis problems. Proton exchange membrane fuel cells (PEMFCs) use hydrogen and oxygen as fuel, and their final product is water. In addition, hydrogen and oxygen can be produced by electrolysis of water to form water cycle energy. PEMFCs have the characteristics of high energy conversion efficiency, zero emissions, and rapid start-up, and have attracted widespread attention, and have become one of the fastest-growing new energy sources. However, the commercialization of PEMFCs for practical applications is still limited by the high cost and low stability of its electrocatalysts.

[0003] The PEMFCs electrocatalyst widely used in the commercial industry is still the Pt / C catalyst. However, due to the shortage and high price of Pt resources, and the ineffective use of platinum atoms inside the existing fuel cell catalyst particles, a large amount of precious metal platinum is used, making the cost of fuel cell engines too high. In addition, the carbon carrier is easily corroded and has a weak binding force with the catalyst particles, which easily causes the platinum particles to fall off and lose, greatly reducing its activity.

[0004] Based on the technical defects of the catalysts currently used in PEMFCs, it is necessary to improve them. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] As one aspect of the present invention, the present invention provides a method for preparing a fluorine-doped nanocatalytic material, which comprises the following steps:

[0007] (1) mixing carbon black and polytetrafluoroethylene, grinding, heating to 500-1000° C. at 1-10° C. / min in a tube furnace, pyrolyzing for 50-100 min, acid washing, heating and stirring, washing, and drying to obtain a CF carrier;

[0008] (2) Disperse the CF carrier in water, mix well, add H2PtCl6 solution, add reducing agent, place in a water bath, filter, wash and dry.

[0009] As a preferred embodiment of the method for preparing the fluorine-doped nanocatalytic material of the present invention: in step (1), the carbon black is Ketjen black, and the mass ratio of Ketjen black to polytetrafluoroethylene is 1:10-100.

[0010] As a preferred embodiment of the method for preparing the fluorine-doped nanocatalytic material described in the present invention: in step (1), the temperature is raised to 500-1000°C at 1-10°C / min in a tube furnace and pyrolyzed for 50-100 min, and the temperature is raised to 900°C at 2°C / min and pyrolyzed for 60 min; the acid washing is carried out with 0.1-1M HCl.

[0011] As a preferred embodiment of the method for preparing the fluorine-doped nanocatalytic material described in the present invention: in step (1), the heating, stirring, washing and drying are performed by stirring in a water bath at 30-100°C for 10-30 hours, then washing with deionized water until neutral, and vacuum drying at 50-100°C for 6-12 hours.

[0012] As a preferred embodiment of the method for preparing the fluorine-doped nanocatalytic material of the present invention: in step (2), dispersing the CF carrier in water is to ultrasonically disperse 10-30 mg of the CF carrier in 10-30 ml of deionized water for 10-30 min.

[0013] As a preferred solution of the method for preparing the fluorine-doped nanocatalytic material described in the present invention: in step (2), the added H2PtCl6 solution is adding 500-1000uL of 10-30Mm / L H2PtCl6·H2O solution.

[0014] As a preferred scheme of the preparation method of the fluorine-doped nanocatalytic material described in the present invention: the adding of the reducing agent, placing in a water bath, filtering, washing and drying is to add 5000-8000uL of 0.1-0.5M / L ascorbic acid solution, place in a 50-80℃ water bath, keep for 2-6h, filter, wash with ethanol and water for 3-5 times respectively, and vacuum dry at 50-100℃ for 6-12h.

[0015] As another aspect of the present invention, the present invention provides an application of the fluorine-doped nanocatalytic material in a fuel cell, wherein: 1-5 mg of the fluorine-doped nanocatalytic material, 500-1000 uL of ethanol, and 1-10 ul of nafion 117 solution are mixed, placed in an ice water bath and ultrasonicated for 10-30 minutes, and then 10-30 uL is drop-coated on a glassy carbon electrode.

[0016] Preferably, 2 mg of the fluorine-doped nanocatalytic material, 800 uL of ethanol, and 5 ul of nafion 117 solution are mixed, placed in an ice water bath for 20 minutes of ultrasonic treatment, and then 15 uL is drop-coated on the glassy carbon electrode.

[0017] Beneficial effects of the present invention: The ultra-low platinum fuel cell catalyst prepared by the present invention combines F-doped carbon material with platinum, and the non-precious metal active sites interact with the platinum active sites, which effectively reduces the amount of platinum used. The F-doped carbon material is used to prepare the CF carrier, which increases the number of active sites and improves the catalyst activity. The F-doped carbon material is used as a carrier to improve the catalyst stability, and it is found that the F-containing carbon material is conducive to the anchoring of platinum and can also improve the dispersion of platinum in the catalyst. The preparation process is simple, easy to operate, and can be quickly prepared. It has excellent oxygen reduction activity and can be used in proton exchange membrane fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following briefly introduces the drawings required for describing the embodiment:

[0019] Figure 1 LSV curves of the C / F carriers in Examples 1, 2, and 3 at different heat treatment temperatures.

[0020] Figure 2 This is a transmission electron microscope image of the C / F carrier in Example 1.

[0021] Figure 3 4 is a comparison chart of the oxygen reduction activity of the electrocatalysts in Examples 4, 5, 6, and 7.

[0022] Figure 4 This is a 50nm scale transmission electron microscope image of the C / F-Pt-K catalyst in Example 4.

[0023] Figure 5 This is a comparison chart of the oxygen reduction activity of different glassy carbon electrode slurries in Examples 8, 9, and 10.

[0024] Figure 6 This is a comparison chart of the oxygen reduction activity of the electrocatalyst of Example 11 and commercial Pt / C.

[0025] Figure 7 This is a comparison chart of the CV of the electrocatalyst in Example 11 before and after 1000 cycles. DETAILED DESCRIPTION

[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.

[0027] Embodiment 1:

[0028] 0.05 g of Ketjen black (ECP-600JD) and 1 g of polytetrafluoroethylene powder (McLean CAS: 9002-84-0) were mixed and ground for 30 min, heated to 900°C at 2°C / min in a tube furnace, and pyrolyzed for 60 min; washed with 0.6 M HCl, stirred in a 60°C water bath for 12 h, then washed with deionized water until neutral, and dried in a 60: vacuum oven for 12 h to obtain the FC-900 carrier, abbreviated as C / F.

[0029] Embodiment 2:

[0030] 0.05 g of Ketjen black and 1 g of polytetrafluoroethylene powder were mixed and ground for 30 min, heated to 800 °C at 2 °C / min, and pyrolyzed for 60 min; acid washed with 0.6 M HCl, stirred in a 60 °C water bath for 12 h, then washed with deionized water until neutral, and vacuum dried at 60 °C for 12 h to obtain the FC-800 carrier.

[0031] Embodiment 3:

[0032] 0.05 g of Ketjen black and 1 g of polytetrafluoroethylene powder were mixed and ground for 30 min, heated to 1000°C at 2°C / min, and pyrolyzed for 60 min; washed with 0.6 M HCl, stirred in a 60°C water bath for 12 h, then washed with deionized water until neutral, and vacuum dried at 60°C for 12 h to obtain the FC-1000 carrier.

[0033] Test: Half-cell test was performed in 0.1M KOH, as Figure 1 As shown in the figure, compared with pure carbon black (CB), FC-800 and FC-1000, the C / F carrier synthesized in Example 1 has the best oxygen reduction activity and is close to the performance of commercial Pt / C. This shows that appropriate high temperature treatment is conducive to the doping of trace fluorine elements and can effectively improve the catalytic activity of oxygen reduction reaction. Figure 2 It can be seen from the TEM image that the C / F carrier presents a regular polyhedral shape.

[0034] Embodiment 4:

[0035] 21 mg of the C / F carrier prepared in Example 1 was ultrasonically dispersed in 30 ml of deionized water for 30 min until uniformly mixed. 901 uL of 30 mM / L H2PtCl6·H2O solution was added under ultrasound, and then 7336 uL of 0.1 M / L ascorbic acid solution was added. The mixture was placed in a 65°C water bath and kept for 4 h. It was filtered and washed with ethanol and water for 3 times respectively, and dried in vacuum at 60°C for 12 h to obtain the fuel cell catalyst C / F-Pt-K.

[0036] Embodiment 5:

[0037] 25 mg of the C / F carrier prepared in Example 1 was ultrasonically dispersed in 25 mL of ethylene glycol (EG) for 30 min, 1073 uL of 30 mM / L H2PtCl6·H2O solution and 1 mL of 0.2 M / L NaOH / EG solution were added, and the mixture was irradiated at a power of 720 W for 90 s in a microwave reactor, filtered, washed three times with ethanol, and vacuum dried at 60°C for 12 h to obtain the fuel cell catalyst C / F-Pt-EG.

[0038] Embodiment 6:

[0039] 21 mg of the C / F carrier prepared in Example 1 was ultrasonically dispersed in 30 ml of deionized water for 30 min until uniformly mixed, 901 uL of 30 mM / L H2PtCl6·H2O solution was slowly added, and stirring was continued for 2 h. The product was filtered and vacuum dried at 60°C for 12 h to collect the product, and then treated in a mixed gas flow of H2 / Ar (1 / 9) at 300°C for 2 h (heating rate of 5°C / min) to obtain a fuel cell catalyst C / F-Pt-H2.

[0040] Embodiment 7:

[0041] Ultrasonic dispersion of 21 mg of the C / F carrier prepared in Example 1 in 30 ml of deionized water for 30 min until uniformly mixed, slowly add 901 uL of 30 mM / L H2PtCl6·H2O solution, and continue stirring for 2 h. Filter, vacuum dry at 60°C for 12 h to collect the product, and then treat it at 800°C in an Ar gas flow for 1 h (heating rate of 5°C / min) to obtain a fuel cell catalyst C / F-Pt-Ar.

[0042] Test: Electrochemical test was carried out in 0.5M2SO4, such as Figure 3 As shown. It can be found that ascorbic acid has the best performance as a reducing agent, and the thermal reduction method with H2 or Ar may cause Pt to agglomerate, thereby reducing the catalytic active centers of the catalyst. Figure 4 The TEM images show the uniform dispersion of Pt particles and the successful doping of F.

[0043] Embodiment 8:

[0044] The fuel cell catalyst C / F-Pt-K prepared in Example 4 was prepared into a slurry for a glassy carbon electrode: 2 mg of catalyst C / F-Pt-K, 800 uL of ethanol, and 5 ul of nafion 117 perfluorinated resin solution were mixed, ultrasonicated in an ice-water bath for 20 min, and then 15 uL was drop-coated on the glassy carbon electrode.

[0045] Test: Electrochemical tests were performed in 0.1 M KOH, as Figure 5As shown in the figure, the slurry with ethanol as dispersant obtained excellent oxygen reduction performance in the test, indicating that the catalyst has the best dispersibility in ethanol, which is more conducive to the dispersion and utilization of Pt active sites.

[0046] Embodiment 9:

[0047] The fuel cell catalyst C / F-Pt-K prepared in Example 4 was prepared into a slurry for a glassy carbon electrode: 2 mg of catalyst C / F-Pt-K, 500 uL of isopropanol, 500 uL of deionized water, and 20 ul of nafion 117 perfluorinated resin solution were mixed, ultrasonicated in an ice-water bath for 20 min, and then 15 uL was drop-coated on the glassy carbon electrode. The electrochemical properties of the catalyst were tested in a half-cell of a three-electrode system.

[0048] Embodiment 10:

[0049] The fuel cell catalyst C / F-Pt-K prepared in Example 4 was prepared into a slurry for a glassy carbon electrode: 2 mg of catalyst C / F-Pt-K, 200 uL of isopropanol, 800 uL of deionized water, and 20 ul of nafion 117 perfluorinated resin solution were mixed, ultrasonicated in an ice-water bath for 20 min, and then 15 uL was drop-coated on the glassy carbon electrode. The electrochemical properties of the catalyst were tested in a half-cell of a three-electrode system.

[0050] Embodiment 11:

[0051] Pour 0.1M perchloric acid into the electrolytic cell, and introduce nitrogen and oxygen into the electrolytic cell respectively. After 30 minutes, the gas reaches saturation in the electrolytic cell. Prepare a glassy carbon electrode according to the method in Example 8. After the slurry is dried, install the electrode on a rotating device, and connect the electrode wire of the electrochemical workstation to reversible hydrogen and a platinum rod, wherein the reversible hydrogen serves as a reference electrode, the platinum rod serves as a counter electrode, and the glassy carbon electrode serves as a working electrode. After the connection is completed, turn on CHI760E. First activate the catalyst, scan 10 CV cycles under saturated N2, and then scan 10 CV cycles under saturated O2, with a scan rate of 50mv / s and a scan potential range of 0.02-1.2V. After scanning 20 CV cycles, scan LSV once under saturated O2 to test its oxygen reduction activity, with a scan rate of 5mv / s and a scan potential range of 0.2-1.05V. Figure 6 As shown in Figure 2, the catalyst has a better oxygen reduction activity than commercial Pt / C. In order to test the stability of the catalyst, 1000 cycles of CV were scanned at a scan rate of 10 mv / s and a scanning potential range of 0.02-1.2 V. Figure 7 As shown, after 1000 cycles, the electrochemical active area remains basically unchanged, indicating that the catalyst has excellent durability.

[0052] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. Application of a fluorine-doped nanocatalytic material in a fuel cell, characterized in that: 2 mg of the fluorine-doped nanocatalytic material, 800 uL of ethanol, and 5 ul of nafion 117 solution were mixed, placed in an ice water bath for 20 min of ultrasonication, and then 15 uL was drop-coated on the glassy carbon electrode; The preparation method of the fluorine-doped nanocatalytic material comprises the following steps: 0.05 g of Ketjen black and 1 g of polytetrafluoroethylene powder are mixed and ground for 30 minutes, heated to 900°C at 2°C / min in a tube furnace, and pyrolyzed for 60 minutes; washed with 0.6 M HCl, stirred in a 60°C water bath for 12 hours, then washed with deionized water until neutral, and dried in vacuum at 60°C for 12 hours to obtain a C / F carrier; Ultrasonic dispersion of 21 mg C / F carrier in 30 ml deionized water for 30 min until uniformly mixed, add 901 uL of 30 mM / L H2PtCl6•H2O solution under ultrasound, and then add 7336 uL of 0.1 M / L ascorbic acid solution. Place the mixture in a 65 ℃ water bath for 4 h, filter, wash with ethanol and water for 3 times respectively, and dry under vacuum at 60 ℃ for 12 h to obtain fluorine-doped nanocatalytic material for fuel cell catalyst.

Citation Information

Patent Citations

  • Modified cobalt-manganese-oxide-doped carbon nanotube catalyst as well as preparation method and application thereof

    CN105552391A

  • Fluorine-doped porous carbon nano material as well as preparation method and application thereof

    CN111266124A

  • Porous carbon platinum-loaded material and preparation method and application thereof

    CN111430731A

  • Platinum-carbon catalyst as well as preparation method and application thereof

    CN114122426A

  • Platinum-carbon catalyst as well as preparation method and application thereof

    CN114122428A